2014
DOI: 10.11646/zootaxa.3873.5.2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation in the Cinnamon Tanager Schistochlamys ruficapillus Aves: Thraupidae)

Abstract: The Cinnamon Tanager Schistochlamys ruficapillus inhabits semi-open grassy country, primarily in Brazil south of Amazonia. Three subspecies are currently recognized, one of which, S. r. sicki, is poorly known and endemic to the central Brazilian savannas (Cerrado). This paper analyses individual and geographic variation in this species on the basis of body measurements and plumage coloration. Larger birds are usually found farther south and at higher elevations, while smaller birds are found farther north and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In this study, more than one ventral plumage pattern was identified in the same localities (e.g., localities from the central Brazil [Goiás], and in the boundaries of southern Brazil and Paraguay), rejecting a possible delimitation among populations. In a recent study about morphological variation in Schistochlamys ruficapillus (Lopes & Gonzaga, 2014), a similar conclusion was proposed; the recognition of the three subspecies in the Cinnamon Tanager were based individuals from distant populations (scarce sampling), and intermediate stages were not included in these descriptions.…”
Section: Delimitation Of the Speciesmentioning
confidence: 75%
“…In this study, more than one ventral plumage pattern was identified in the same localities (e.g., localities from the central Brazil [Goiás], and in the boundaries of southern Brazil and Paraguay), rejecting a possible delimitation among populations. In a recent study about morphological variation in Schistochlamys ruficapillus (Lopes & Gonzaga, 2014), a similar conclusion was proposed; the recognition of the three subspecies in the Cinnamon Tanager were based individuals from distant populations (scarce sampling), and intermediate stages were not included in these descriptions.…”
Section: Delimitation Of the Speciesmentioning
confidence: 75%